Integrated application of macrophytes and zooplankton for wastewater treatment - Prakash, Diwakar; Kumar, Ram; Rajan, Kumar; Patel, Abhishek; Yadav, Devesh Kumar; Dhanker, Raunak; Khudsar, Faiyaz A. (Frontiers in Environmental Science, 2022)
The increasing amount of sewage has become a serious concern globally, demanding sustainable solutions. The constructed wetlands system (CWS) can be installed at wastewater discharge site and properly screened biopurifiers can be used for efficient wastewater treatment. Filter-feeding zooplankton has the potential to graze on bacteria and reduce biological oxygen demand. However, higher suspended particles choke the zooplankton filtering appendages. Integrated application of zooplankton and macrophytes can solve the problems by reducing contaminants and providing surface area for zooplankton to take refuge. Using three different approaches: (a) screening of natural bio purifiers through time series study, (b) assessment of sewage treatment potential of screened biopurifiers in CWS and (c) evaluation of the growth potential of screened biopurifiers in untreated wastewater, this study explored combined use of macrophyte and zooplankton in CWS. The three-year time series study in the vicinity of the wastewater discharge area in - recorded the zooplankton, Brachionus angularis, and Moina macrocopa as highly indicative zooplankton. Top two highly indicative macrophytes were Typha and Phragmites. In laboratory conditions, the population growth rates of B. angularis and M. macrocopa were significantly higher in wastewater without any external nutrient source than in control with algae as food source. Integrated application of zooplankton, (B. angularis, M. macrocopa) macrophytes (Typha, Phragmites) in CWS yielded upto 56% reduction of total bacterial count and upto 92% reduction of BOD along with substantial increase in DO level. The present results strongly suggest the use of CWS planted by macrophytes and inoculated by zooplankton. The usefulness of this system is further supported by the natural occurrence of selected species, as it’s easy to maintain, has low installation cost and excellent efficiency in treating wastewater. As, both the zooplankton species are preferred live feed for rearing of fish larvae the present results suggest the use of zooplankton and macrophytes for treatment of wastewater, reduction of sludge, and harvest of live feeds for aquaculture industry to augment circularity and promote decentralized wastewater treatment.